Correction: Lavie and Mayer (2025). Navigating Emotional Labor and Social Exchange in Hospitality: A Comparative Study of Food and Beverage Workers in Tel Aviv and New Orleans During COVID-19. Social Sciences 14: 143 - Noa Lavie; Vicki Mayer (Social Sciences, 2025)
Deleting and Replacing Citation [...]